Data‐poor stock assessment of fish stocks co‐exploited by commercial and recreational fisheries: Applications to pike Esox lucius in the western Baltic Sea - Gemert, Rob; Koemle, Dieter; Winkler, Helmut; Arlinghaus, Robert (Fisheries management and ecology, 2022)
Information on catch and effort of recreational angling in mixed‐use fisheries (co‐exploited by commercial and recreational fishers) is often scarce, preventing the application of data‐rich stock assessments typically performed for industrialised commercial fisheries. This study shows how data‐poor stock assessment methods developed for marine fisheries, particularly a model class labelled as “catch‐only” models (COMs), offer a possible solution. As a case study, COMs are used to assess a northern pike Esox lucius L. stock around the German Baltic island of Rügen. Multiple COMs were fitted to a time series of total pike removals, and their outputs were used as explanatory variables in ensemble models. The stock was found to be fully exploited and currently declining. This study highlights the potential for using COMs to determine status of previously unassessed coastal and freshwater stocks facing recreational fishing pressure and demonstrates how incorporating recreational removals is crucial for achieving reliable insights into the status of mixed‐use stocks.